+0  
 
0
448
1
avatar+587 

What is (f⋅g)(x)?

 

f(x)=x^2+2x−6

g(x)=x^4+3

 Mar 6, 2018

Best Answer 

 #1
avatar+8963 
+2

(f⋅g)(x)

 

=   f(x) * g(x)

 

=   (x2 + 2x - 6) * (x4 + 3)

 

=   x6 + 3x2 + 2x5 + 6x - 6x4 - 18

 

=   x6 + 2x5 - 6x4 + 3x2 + 6x - 18

 Mar 6, 2018
 #1
avatar+8963 
+2
Best Answer

(f⋅g)(x)

 

=   f(x) * g(x)

 

=   (x2 + 2x - 6) * (x4 + 3)

 

=   x6 + 3x2 + 2x5 + 6x - 6x4 - 18

 

=   x6 + 2x5 - 6x4 + 3x2 + 6x - 18

hectictar Mar 6, 2018

25 Online Users

avatar
avatar
avatar